Petrophysical facies characteristics and classification evaluation of Dongying Formation of Nanpu No. 4 structure - Jingying Chen; Jingbo Zeng; Jianbin Zhao; Qiuli Yin; Airong Niu (地球与行星物理论评, 2024)
Strong diagenesis and reservoir heterogeneity as well as complex pore structure in the late stage of No. 4 structure in Nanpu sag make assessment of the petrophysical characteristics of its high-quality reservoir and evaluation of its effectiveness difficult. To address this, the sedimentary, diagenetic, and pore structure characteristics of the reservoir were comprehensively studied using core thin section analysis, scanning electron microscopy, X-ray diffraction, capillary analysis, and logging and oil tests. The results showed that the sedimentary facies of the Ed2 and Ed3 of the study area were mainly braided river delta types, and the sedimentary microfacies mainly developed in an underwater distributary channel, interdistributary bay, and mouth bar. Diagenetic facies can be divided into four types based on diagenesis and mineral types: weak dissolution facies, clay mineral filling facies, carbonate cementation facies, and compacted dense facies. The pore structure facies can be divided into four types based on the reservoir physical properties and mercury injection, I: macropore coarse throat type, II: macropore medium throat type, III: mesopore thin throat type, and IV: micropore throat type. Based on the superimposed cluster analysis of sedimentary, diagenesis, and pore structure, the reservoir petrophysical facies can be divided into PF1-PF4, and the corresponding quantitative classification and evaluation criteria can be established. PF1 is an advantageous reservoir with high oil, gas, and water productivity; PF2 is an oil-bearing reservoir with average productivity; PF3 is a poor reservoir with low productivity after reservoir reconstruction; and PF4 is an invalid reservoir. The quantitative classification and evaluation criteria of petrophysical facies are established by logging response rules, which provide technical support and a solid theoretical basis for the evaluation of reservoir effectiveness, superior reservoir prediction, and subsequent ongoing development in the study area.